2016
DOI: 10.1158/1940-6207.capr-15-0400
|View full text |Cite
|
Sign up to set email alerts
|

Early Events in the Molecular Pathogenesis of Lung Cancer

Abstract: The majority of cancer-related deaths in the United States and worldwide are attributed to lung cancer. There are more than 90 million smokers in the United States who represent a significant population at elevated risk for lung malignancy. In other epithelial tumors, it has been shown that if neoplastic lesions can be detected and treated at their intraepithelial stage, patient prognosis is significantly improved. Thus, new strategies to detect and treat lung preinvasive lesions are urgently needed in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
82
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 132 publications
2
82
0
2
Order By: Relevance
“…This is largely attributed to late diagnosis after locoregional or distant spread [1]. Advances (e.g., molecular-based) in early detection and prevention of NSCLC have been limited by a poor understanding of early changes in NSCLC pathogenesis [3]. …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is largely attributed to late diagnosis after locoregional or distant spread [1]. Advances (e.g., molecular-based) in early detection and prevention of NSCLC have been limited by a poor understanding of early changes in NSCLC pathogenesis [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that LUADs and LUSCs carry different genomic landscapes of driver mutations as well as disparate clinicopathological features [3]. While LUSCs are diagnosed almost exclusively in smokers, LUADs are known to develop in both smokers and non-smokers [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations